Critical Contextual Elements in Facilitating and Achieving Success with a Person-Centred Care Intervention to Support Antipsychotic Deprescribing for Older People in Long-Term Care. (8th July 2018) - Chenoweth, Lynn; Jessop, Tiffany; Harrison, Fleur; Cations, Monica; Cook, Janet; Brodaty, Henry
Abstract : Antipsychotic and other tranquilising medicines are prescribed to help care staff manages behaviour in one-quarter of older people living in Australian long-term care homes. While these medicines pose significant health risks, particularly for people with dementia, reliance on their use occurs when staff are not educated to respond to resident behaviour using nonpharmacological approaches. The Halting Antipsychotic use in Long-Term care (HALT) single-arm study was undertaken to address this issue with 139 people 60 years and over with behaviours of concern for staff living in 24 care homes. A train-the-trainer approach delivered person-centred care education and support for 22 HALT (nurse) champions and 135 direct care staff, dementia management education for visiting general practitioners (GP) and pharmacists, use of an individualised deprescribing protocol for residents, and awareness-raising for the resident's family. The HALT champions completed open-ended questionnaires and semistructured interviews to identify the contextual elements they considered most critical to facilitating, educating care staff, and achieving success with the study intervention. They reported that person-centred approaches helped care staff to respond proactively to resident behaviours in the absence of antipsychotic medicines; the champions considered that this required strong managerial support, champion empowerment to lead change, reeducation of care staff, and the cooperation of families and GPs.